Altered microstate C and D dynamics in high social anxiety: a resting-state EEG study - Zhang, Huoyin; Peng, Binyu; Liu, Yutong; Xi, Yu; Lei, Yi (Frontiers in Psychology, 2025)
IntroductionSocial anxiety is characterized by excessive fear of negative evaluation and avoidance in social situations. While its neural processing patterns are well-documented, the millisecond-level temporal dynamics of brain functional networks remain poorly understood. This study used EEG microstate analysis to explore the dynamic neural mechanisms underlying social anxiety.MethodsEyes-closed resting-state EEG data were collected from 41 participants, divided into high social anxiety (n = 23) and low social anxiety (n = 18) groups based on their Liebowitz Social Anxiety Scale (LSAS) scores. EEG microstate parameters, including duration, occurrence frequency, time coverage, and transition probabilities, were analyzed. Correlation analyses were conducted between LSAS scores and microstate dynamics.ResultsThe high social anxiety group exhibited significantly increased duration and coverage of microstate C (associated with processing personally significant information and self-reflection) and decreased duration and coverage of microstate D (associated with executive functioning). Transition probabilities involving microstate C (A ↔ C, B ↔ C) were significantly higher, while those involving microstate D (A ↔ D) were significantly lower in the high social anxiety group. In the low social anxiety group, B ↔ C transition probability showed significant negative correlations with LSAS total and avoidance subscale scores.DiscussionThese findings reveal distinct neural dynamics in social anxiety, characterized by heightened self-referential processing (microstate C) and impaired executive functioning (microstate D). The altered transition patterns suggest a predisposition for excessive self-focus and reduced coordination with executive control networks in high social anxiety individuals. These results provide new insights into the neural mechanisms of social anxiety and offer potential directions for clinical interventions and early detection.